Peculiarities of using innovation pedagogical technologies in the professional training of future specialists of service sector - Y. Lukashevych (Професійна освіта: методологія, теорія та технології, 2022)
The article deals with the importance and advantage of using innovation pedagogical technologies in professional preparation of future specialists of service sector that provides the development of professional, creative competencies and stimulates the future specialists’ need in self-education. It is emphasized that, thanks to the use of innovative technologies, the forms of modern lectures and practical classes are expanded and diversified: the quality of presentation of the material and efficiency of its assimilation are improved, the skills of informational and communicative interaction are formed, the worldview of students expands, and motivation for the chosen profession increases. The purpose of the article is to define the specific features of the application of innovative pedagogical technologies in the professional training of future specialists of the service sector in higher education institutions. The following methods have been used in the research as analysis, synthesis, systematization of the psychological and pedagogical literature, generalization. Results. The scientific and pedagogical analysis of literatures has allowed the author to specify the following peculiarities of innovation pedagogical technologies: 1) the personality of a teacher or an organizer of the educational process is leading, but this changes its position in relation to the student and to himself/herself; 2) the teacher appears not only as a carrier of knowledge and information, norms and traditions, but contributes of formation and development of student’s personality. The research results may contribute to optimization and improvements of teaching in the establishments of higher education by means of innovation pedagogical technologies. Conclusion. Among a wide range of innovation pedagogical technologies of the most significant for preparation of future service sector specialist are personally-oriented technologies, technologies of project and problem teaching, information-communicative, interactive technologies. The study of professional disciplines with using of problem style of learning of teaching material, conducting independent researches, the result of which is creation of training projects on actual themes, allow to increase cognitive interest, induce of students as future service sector specialists to active acquisition of professional knowledge, skills, develop mental abilities, creation of strong base for deep professional preparation of future service sector specialists